The Specifics of Students' Self-Control - Kholmurotovna , Avezova (Indonesian Journal Publisher, 2025)
In the life and work of every person, the problem of regulating activity in the changing conditions of the surrounding existence is of great importance. According to modern views, the meaningful description of the entire psyche of a person is the self-regulation of goal-oriented activity, the ability to